Complete mitochondrial genomes of two snail mite: Riccardoella tokyoensis and R. reaumuri (Acariformes, Prostigmata, Ereynetidae). Issue 2 (1st February 2022) - Hiruta, Shimpei F.; Waki, Tsukasa; Shimano, Satoshi
Abstract: We determined the mitochondrial genome sequences of two snail mites, Riccardoella tokyoensis and R. reaumuri . The length of the entire mitogenome of these two species is 15, 078 bp and 15, 148 bp long, respectively. Both of them contain 13 proteins, two rRNAs, and 22 tRNAs for a total of 37 gene products. The gene order of Riccardoella is able to explain by a single rearrangement event from that of other Eupodina species; the whole region, including both rRNA genes and control region (CR), is inverted at the same position. The CR including a tandem repeat region in both of the mitogenomes of Riccardoella species.